Mutation patterns in the HBB gene determine the frequency and onset of blood transfusion in patients with beta-thalassemia major and HbE-beta thalassemia - Tasnim, Raisa (Brac University, 2020)
This thesis report is submitted in partial fulfilment of the requirement for the degree of Master of Science in Biotechnology, 2019.